The Effect of PhET Simulation-Based Learning on The Ability to Understand Elementary Science Concepts in Work and Energy Material - Bahtiar, Bahtiar; Ibrahim, Ibrahim; Maimun, Maimun (STKIP HARAPAN BIMA, 2024)
This research aims to determine the effect of using PhET Simulation on understanding Natural Science concepts in prospective teachers, with a focus on the material